Personnel/human resource management - Heneman, Herbert G. III.; Schwab, Donald P.; Fossum, John A. (New Delhi : Universal Book Stall, 1993)
This book continues to built around the Personnel/Human Resource (P/HR) management model. The model, however, has been placed in a broader strategic and administrative context. This edition is divided into nine parts. Part 1. Personnel/human resource management and its environment. Part2. Individuals and jobs. Part 3. Assessing personnel/human resource management outcomes. Part 4. Human resource planning. Part 5. External staffing. Part 6.Internal staffing and development. Part 7. Compensation. Part 8. Labor relations. Part 9. Work environment.
Includes bibliographical references and index.
hza 19/07/2018
Loans
Keywords: Personnel management